Design and Analysis of Loss-of-lubrication Capacity of Helicopter Reducer - Wusheng Song; Changsheng Yang (Jixie chuandong)
Based on the analysis of the results of the loss-of-lubrication test of helicopter reducer， the design and analysis method of the loss-of-lubrication capacity of reducer is studied from the aspects of gears， bearings， casing， lubrication system and lubricating medium. The detailed design of parts and components in the design stage of reducer is guided. The loss-of-lubrication test method is analyzed. The method is verified by the loss-of-lubrication test of design examples. The situations that only rely on prototype test results can be relied on to optimize the design in the past is changed， and the guiding opinions of previous loss-of-lubrication test conclusions are improved.